Underlying research philosophical orientation in social science research: Positivism vs. Interpretivism / Siti Arpah Noordin - Noordin, Siti Arpah (2011)
Before adopting certain methodologies, it is important for researcher to understand the framework of research methodology. Remenyi, Williams, Money, and Swartz (1998) define research methodology as a procedural framework within which the research is conducted. They emphasize that in any research work, researcher should consider many factors before choosing appropriate methodology with the topic or subject to be researched and making the specific research questions as the main drivers. There are also several areas to be considered in deciding research method suggested in the literature, which include the context of the study or phenomenon, the research goals, the level and nature of research questions, practical reflection and resources availability. On the other hand, in general many recognize that the researcher's personal philosophy and beliefs have some influences on the research method adopted (Crossan, 2002; Shih, 1998; Proctor, 1998; Denzin and Lincoln 1994). The traditional perspective of research methodology states that there are two general approaches - the quantitative and qualitative research. Conversely, how a researcher conducts research activity may be influenced by the researcher's philosophical stance. According to Benton and Craib (2001), philosophy provides 'foundations' for the research done in particular scientific specialisms. Easterby-Smith, Thorpe and Lowe (2002) suggests that understanding philosophy helps to refine and specify which research methods to be used to clarify the type of evidence gathered and its source as to answer the research questions; to evaluate different methodologies and methods that could avoid inappropriate use of methods and to be creative and innovative in either selection or adaptation of methods. This article discusses the rationale of choosing appropriate research approach by discussing the paradigm of interpretivist and positivits which normally associated with the qualitatitive and quantitative research approach.